High pressure processing applied for enhancing the antioxidant content of minimally processed peaches - Denoya, Gabriela Inés; Polenta, Gustavo Alberto; Apóstolo, Nancy Mariel; Budde, Claudio Olaf; Cristianini, M.; Vaudagna, Sergio Ramon (Wiley, 2021)
In addition of the capacity of High-Pressure Processing (HPP) to preserve fruits, recent studies highlight the ability of this technology to increase the content of antioxidants. The aim of this work was to find the HPP conditions able to maximize the increase in antioxidants in minimally processed peaches without affecting the overall quality, complemented by a microstructural study to better understand the observed effects. Therefore, minimally processed peaches were subjected to HPP-treatment with different pressure levels (100, 300, 500 MPa) and holding times (1,5 min). Results showed that 300 and 500 MPa induced a significant increase in the antioxidant content, which can be partially linked to the increase in the extractability of these compounds brought about by the changes in the microstructure. It can be concluded that a treatment at 300 MPa for 1 min is enough to induce a significant increase in antioxidants, without causing deterioration of the product.